Reinterpretation of the University idea; implications for nursing education - Annatjie Botes (AOSIS, 1997)
Transformation is the order of the day in South African society. Opsomming Transformasie is huidiglik aan die orde van die dag in die Suid-Afrikaanse gemeenskap. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.